THE EFFECTIVENESS OF BL32 ACUPRESSURE TECHNIQUE ON PAIN DURING THE FIRST STAGE OF LABOR - Rahmi, Junaida; Sari, Yollin Noviana; Haryanto, Sri; Romlah, Siti Novy; Katmini, Katmini; Meri, Diana (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2025)
ABSTRACTBackground: Psychologically, pain during childbirth can cause mothers to have difficulty interacting, which can make it difficult for them to express their feelings. One non-pharmacological approach is acupuncture. Acupuncture points associated with reducing pain intensity during childbirth include BL 32. Research Objective: To determine whether there is a difference in the effectiveness of the BL 32 acupuncture technique on pain during childbirth in the first stage of labor. Research Method: Quasi-experimental with a pre-test and post-test design. The sample size used in this study was a minimum of 30 respondents. The sampling technique used in this study was total sampling. The data were then analyzed using a parametric test with an Independent T-Test. Research Results: The pain level identified in mothers in the active phase I of labor before being given the BL32 acupressure technique intervention was 7.53 in the pre-test and 6.60 in the post-test, with an asym. Sig (2-tailed) value of 0.001. Conclusion: There is a significant difference between the BL32 acupressure technique and the control group. ABSTRAKLatar Belakang: Secara psikologis, nyeri persalinan dapat mengakibatkan ibu mengalami kesulitan untuk berinteraksi yang dapat menyebabkan ibu sulit mengungkapkan perasaannya. Salah satu upaya non farmakologi adalah akupresur. Titik-titik akupresur yang terkait dengan penurunan intensitas nyeri saat persalinan diantaranya adalah BL 32 . Tujuan Penelitian: untuk melihat apakah ada perbedaan efektifitas teknik akupresur BL 32 terhadap nyeri persalinan pada kala I. Metode Penelitian: quasy eksperiment dengan pendekatan pre test dan post test design. Besar sampel yang digunakan dalam penelitian ini ialah dengan menggunakan sampel minimam sebanyak 30 responden. Teknik sampel dalam penelitian ini mengunakan teknik sampel total sampling. Data kemudian dianalisis menggunakan uji parametrik dengan Independent T-Test. Hasil Penelitian: Terindentifikasi tingkat nyeri yang pada ibu bersalin kala1 fase aktif sebelum diberikan intervensi teknik akupresur BL32 yaitu tingkat terbesar pretest adalah 7.20 dan nilai terbesar postest adalah 6.07 dengan asym. Sig (2-tailed) bernilai 0.001.